HOMEOBOX2, the paralog of SIX-ROWED SPIKE1/HOMEOBOX1, is dispensable for barley spikelet development - Thirulogachandar, Venkatasubbu (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology.